Effectiveness of avatar-based technology in patient education for improving chronic disease knowledge and self-care behavior: a systematic review. (June 2019) - Wonggom, Parichat; Kourbelis, Constance; Newman, Peter; Du, Huiyun; Clark, Robyn A.
ABSTRACT: Objective: The objective of the review was to examine the effectiveness of patient education using avatar-based technology on knowledge and self-care behaviors in patients with chronic disease. Introduction: Chronic disease is a major global problem. Patients with chronic disease who engage in self-care and self-management of their illnesses have better health outcomes and fewer hospitalizations and complications. Currently, information and communication technologies are used to support self-care and improve health outcomes. Within the body of literature, research into avatar-based technology for patient education is growing rapidly. To date, the evidence has not been systematically reviewed to determine the effectiveness of patient education using avatar-based technology on patients' knowledge and self-care behaviors in chronic disease. Inclusion criteria: This review included studies of children and adults who have received avatar-based patient education interventions. The comparator was usual care or other forms of educational programs. The outcomes were knowledge, self-care behavior, self-efficacy, health-related quality of life, readmission and medication adherence. Experimental designs were eligible, including non-randomized controlled trials, and quasi-experimental, prospective and retrospective before and after studies. Methods: Seven databases, including MEDLINE, CINAHL, PsycINFO, Cochrane Central Register of Controlled Trials, ProQuest, Web of Science, Scopus and three other trial registries, including the World Health Organization (WHO), ClinicalTrials.gov and Australian New Zealand Clinical Trials Registry, were systematically searched for studies published between January 2005 and March 2017. Papers selected for retrieval were assessed by two independent reviewers for methodological validity prior to inclusion in the review using the standardized critical appraisal instrument from the Joanna Briggs Institute System for the Unified Management Assessment and Review of Information (JBI SUMARI). Data extracted from papers included specific details about the interventions, populations, study methods and outcomes significant to the review question and specific objectives using the standardized data extraction tool from JBI SUMARI. Due to heterogeneity among the included studies, statistical pooling and meta-analysis were not possible. The results were tabulated, and the data narratively synthesized. Results: Nine publications from eight studies were included in this review (n = 752). Three out of the eight studies were randomized controlled trials and five were non-randomized experimental studies. The overall quality of the included studies was moderate. There was a low risk of bias for the randomized controlled trial studies and moderate risk of bias for the quasi-experimental studies. Four of the eight studies showed that patients who participated in avatar-based education had a statistically significant improvement in knowledge ( p < 0.05). Three studies showed improvement in behaviors and self-efficacy. Only three of eight studies examined health-related quality of life and adherence to medication, but the results were not statistically significant ( p > 0.05). No studies identified the effectiveness of avatar-based patient education on readmission. Conclusions: Avatar-based technology in patient education can have a positive effect on a wide range of healthcare outcomes. The intervention can improve knowledge, self-care behaviors and self-efficacy in patients with chronic diseases. However, there is limited evidence of improvement in health-related quality of life and adherence to medication, and no available research on readmission.